Almost the Same, but Not Quite: Re-Orienting the Story of the Subject in Christina Fernández Cubas's El año de Gracia - Jessica A. Folkart (Studies in 20th & 21st Century Literature, 2002)
Cristina Fernández Cubas's novel El año de Gracia (1985), about a young Spaniard who is shipwrecked on a deserted island with only a mangy shepherd for company, evokes the political dialectics of self/other found in the European's discovery and conquest of an unknown island in Robinson Crusoe. In Fernández Cubas's literary depiction of the European subject, however, she situates him on the margins of power in order to view the dynamic from a different perspective. The postcolonial theorizations of Edward Said and Homi Bhabha inform this analysis of how Fernández Cubas's castaway is at first overpowered by the other and then, in his struggle for control, comes to appreciate and learn from those different qualities instead of subsuming them beneath his personal dominance. While the Spanish novel clearly foregrounds Robinson Crusoe as its model text, it also reorients the once supreme subject in the site of exclusion. Hence this protagonist tells his story from a newly formed, hybrid perspective of the oppressor and the oppressed melded into one. El año de Gracia engages conflicting visions of power in dialogue with one another, interrogating the borders that define them according to the differences they exclude. In the process, it disorients the subject in order to reorient the story that he tells as one that is almost the same as its literary forebear but, importantly, not quite.
Keywords: Christina Fernández Cubas; El año de Gracia; politics; self; other; Europe; Robinson Crusoe; power; postcolonialism; castaway; control; dominance; oppressor; oppressed